Exploitation traditionnelle des végétaux spontanés en région sahélienne du Burkina Faso - Souleymane Ganaba; Jean Marie Ouadba; Ouétian Bognounou (VertigO)
The Sahel region is characterised by forestry resources exploitation for making tools, household utensils, chattels and others admittedly usefulness products.  The aim of this study conducted by surveying in sahelian villages and by farm observations is to characterise the traditional knowledge of forestry resources used by different ethnic groups and their impact on resources evolution. Moreover, an economic attempt to escape this kind of forestry resources exploitation is done. Many cultivation and keeper tools, chattels, household utensils are made with forestry resources. The plants used for every forestry produce is variable with the existence or abundance of the species and the sociologic and cultural consideration peculiar to each ethnic group like choice of fuel wood. The different exploitation forms more or less severe had been contributed to amplify the climatic dryness effects on forestry resources degradation. Fortunately, an evolution with manufactured products enable to adapt environment changes. There is an imperious necessity to document, consider and to improve indigenous knowledge of natural resources for sustainable development